Frequency of Causes of Female Infertility Diagnosed Through Laparoscopy in Females Presenting in a Tertiary Care Hospital - Mahwish Saif, Sadia Mustafa, Binyamin Butt (Journal of Rawalpindi Medical College, 2022)
OBJECTIVE To report the frequency of causes of female infertility by laparoscopy in females presenting in a tertiary care hospital MATERIALS & METHODS Study design: Cross sectional study Setting: Department of Obstetrics & Gynecology, Shalimar Hospital, Lahore Duration of study: July 01, 2020, till July 31, 2021 DATA COLLECTION PROCEDURE: A total of 370 females fulfilling selection criteria were selected from operation theatre of Department of Obstetrics and Gynecology, Shalimar Hospital Lahore. Informed consent was obtained from each case. Demographic information (name, age, BMI, duration of marriage, type of infertility, and parity) will also be noted. Then females underwent laparoscopy under general anesthesia by researchers. On laparoscopy, the pelvis was inspected, including uterus, fallopian tubes, round ligaments, uterovesical pouch, uterosacral ligaments, and Pouch of Douglas. The tubes were inspected for any abnormality in their length and shape and patency was checked by retrograde dye test. Both ovaries were examined regarding their size, shape, thickness of peripheral follicles, evidence of ovulation and their relationship with fimbrial end of the tubes. Peritubal, periovarian and omental adhesions, tubo-ovarian masses, endometriotic deposits, fibroid, presence of fluid in the Pouch of Douglas or any other pathology, if present was noted. Data was entered and analyzed in SPSS version 21.0. RESULTS: The mean age of our cases was 33.93 ± 5.81 years with minimum and maximum ages of 18 and 45 years. According to the etiology of infertility, 5(1.4%) cases had unexplained infertility, 140(37.8%) cases had tubal infertility, 60(16.2%) cases had polycystic ovaries, 41(11.1%) cases had Peritubal and peri-ovarian adhesion, 71(19.2%) cases had endometriosis, 38(10.3%) females had fibroids and 20(5.4%) cases had an ovarian cyst. CONCLUSION: We conclude that on diagnostic laparoscopy the frequency of causes of female infertility was found to be tubal infertility (37.8%), followed by endometriosis (19.2%), polycystic ovaries (16.2%), Peri-tubal and peri-ovarian adhesion (11.1%), fibroids (10.3%), ovarian cyst (5.4%), unexplained infertility (1.4%).